Exploring health literacy in patients with chronic diseases in Chongqing, China: a cross-sectional study - Yu Zhao; Hongyan Liu; Yong Zhao; Yaxin Liu; Yao Chen; Huan Zeng; Manoj Sharma; Jun Yuan; Yaqi Wen; Chengbin Wu; Weiyun Lai; Xiangxi Zhou (BMJ Open, 2023)
Objectives Personal health literacy is the degree to which individuals have the ability to find, understand and use information and services to inform health-related decisions and actions for themselves and others. Health literacy levels remain low, despite the many measures that have been taken to improve it. In addition, the number of patients with chronic diseases is increasing. Our study aimed to explore the different aspects and factors influencing health literacy among patients with chronic diseases in Chongqing, China.Design Cross-sectional study.Setting and patients This study was conducted in Chongqing using the 2018 National Questionnaire on Health Literacy of Residents administered to 27 336 patients with chronic diseases.Outcome measures The prevalence and factors of health literacy in patients with chronic diseases.Results Among the patients who participated in the study (n=27 336), 51.3% were males. Only 21.6% of the patients with chronic diseases had adequate health literacy (questionnaire score was equal to or exceeded 80% of the total questionnaire score). Patients with chronic diseases aged 25–34 years (OR=1.18, 95% CI 1.02 to 1.36) and 35–44 years (OR=1.18, 95 % CI 1.03 to 1.35) had higher health literacy than patients aged 65–69 years. Patients from rural areas had higher health literacy levels than those from urban areas (OR=0.92, 95% CI 0.86 to 1.00). Furthermore, married patients had lower health literacy than unmarried patients (OR=0.88, 95% CI 0.80 to 0.97). Patients who were illiterate or slightly literate (OR=0.10, 95% CI 0.08 to 0.12) had lower health literacy than patients who were in junior college or had a bachelor’s degree or above. In addition, non-farmers had higher health literacy levels than farmers (OR=1.18, 95% CI 1.08 to 1.28). In terms of inadequate health literacy, patients who self-rated themselves as healthy had higher health literacy than those who self-rated as unhealthy (OR=1.80, 95% CI 1.33 to 2.43).Conclusions The health literacy of patients with chronic conditions remains at a low level and varies significantly with their demographic and social characteristics. These findings indicate that targeted interventions may be useful to improve health literacy in patients with chronic conditions in China.